1975
DOI: 10.1121/1.2001927
|View full text |Cite
|
Sign up to set email alerts
|

Existence of the acoustic cricothyroid response in the rat

Abstract: A recent investigation by P. H-S. Jen et al. [J. Acoust. Soc. Am. 57, S42 (A) (1975)] has shown that during acoustic stimulation the cricothyroid musclc (CTM) responds in echolocating bats. Previous studies have shown that the rat emits ultrasonic cries which can be used to echolocate. Our study attempts to determine the existence of the acoustic CTM response in this species. Electromyography of the CTM was obtained in ten rats. Rats were stimulated with pure tones between 5 and 60 kHz. During acoustic stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Short-latency acoustico-laryngeal reflexes have been observed in several nonhuman species (Jen and Suga, 1976;Suzuki and Sasaki, 1977;Yonovitz et al, 1975). Also, it has been demonstrated that auditory stimulation can elicit short-latency reflex responses in several human cranial and spinal muscle systems (Luschei et al, 1967 Rasmussen, 1946;Torvik, 1956;and Wright and Barnes, 1972).…”
Section: Introductionmentioning
confidence: 98%
“…Short-latency acoustico-laryngeal reflexes have been observed in several nonhuman species (Jen and Suga, 1976;Suzuki and Sasaki, 1977;Yonovitz et al, 1975). Also, it has been demonstrated that auditory stimulation can elicit short-latency reflex responses in several human cranial and spinal muscle systems (Luschei et al, 1967 Rasmussen, 1946;Torvik, 1956;and Wright and Barnes, 1972).…”
Section: Introductionmentioning
confidence: 98%